Gas Chromatographic Determination of Cyprodinil, Fludioxonil, Pyrimethanil, and Tebuconazole in Grapes, Must, and Wine - Cabras, Paolo; Angioni, Alberto; Garau, Vincenzo L.; Meselli, Elizabeth V. [UNESP] (My University, 1997)
A rapid and simple gas chromatographic method for determinating cyprodinil, fludioxonil, pyrimethanil, and tebuconazole in grapes, must, and wine is described. An on-line microextraction method was used with a one-step extraction-partition procedure. Nitrogen-phosphorus and mass spectrometric detectors were used, because of their low sensitivity and high selectivity. Because of high selectivity of detector, no cleanup was necessary and the extract was concentrated 5 times. Recoveries from fortified grapes, must, and wine ranged from 93 to 110%. Limits of determination were 0.05 mg/kg for cyprodinil and pyrimethanil and 0.10 mg/kg for fludioxonil and tebuconazole.
Keywords: 1,3 dioxolane derivative; cyprodinil; fludioxonil; fungicide; nitrogen; pesticide residue; phosphorus; pyrimethanil; pyrimidine derivative; pyrrole derivative; tebuconazole; triazole derivative; chemistry; food analysis; fruit; gas chromatography; mass fragmentography; reproducibility; standard; wine; Chromatography, Gas; Dioxoles; Food Analysis; Fruit; Fungicides, Industrial; Gas Chromatography-Mass Spectrometry; Nitrogen; Pesticide Residues; Phosphorus; Pyrimidines; Pyrroles; Reference Standards; Reproducibility of Results; Triazoles; Wine